The Birth of NASA The Work of the Space Task Group, America's First True Space Pioneers - von Ehrenfried, Dutch; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This is the story of the work of the original NASA space pioneers; men and women who were suddenly organized in 1958 from the then National Advisory Committee on Aeronautics (NACA) into the Space Task Group. A relatively small group, they developed the initial mission concept plans and procedures for the U. S. space program. Then they boldly built hardware and facilities to accomplish those missions. The group existed only three years before they were transferred to the Manned Spacecraft Center in Houston, Texas, in 1962, but their organization left a large mark on what would follow. Von Ehrenfried's personal experience with the STG at Langley uniquely positions him to describe the way the group was structured and how it reacted to the new demands of a post-Sputnik era. He artfully analyzes how the growing space program was managed and what techniques enabled it to develop so quickly from an operations perspective. The result is a fascinating window into history, amply backed up by first person documentation and interviews.
Part I Introduction -- The Sputnik Reaction -- The President -- The National Security Council -- The Congress -- Department of Defense/Other -- Part II Creating the Space Team -- Creation of the STG -- The AVRO Canadians -- The Astronauts and Aeromedical -- The Need for More People -- Contractors & Representatives -- The STG Organization -- The End of the STG on November 1, 1961 -- Summary of Key Project Mercury Decisions/Lessons Learned -- Part III Achievements -- Facilities Created for Project Mercury -- Mission Designs and Concepts -- The Impact of the STG on History -- APPENDICES -- Bibliography -- Credits -- Glossary -- About the Author -- Index.
Keywords: Popular works; History; Space sciences; Astronomy; Aerospace engineering; Astronautics; Popular Science; Popular Science in Astronomy; Aerospace Technology and Astronautics; Extraterrestrial Physics, Space Sciences; History of Science; Electronic books